The Effect of Salvia Officinalis on Hot Flashes in Postmenopausal Women: A Systematic Review and Meta-Analysis - Maryam Moradi; Vahid Ghavami; Azin Niazi; Fatemeh Seraj Shirvan; Saye Rasa (Shiraz University of Medical Sciences, 2023)
Background: The experience of hot flashes during menopause has a negative effect on quality oflife and can cause disturbance in the workplace and disrupt daily activities. Phytoestrogens in Salviaofficinalis reduce menopause symptoms due to their anti-dopaminergic effects. This study wasconducted to systematically review and summarize the results of clinical trials on the effect of Salviaofficinalis on hot flashes in postmenopausal women.Methods: In this systematic review, databases including Pubmed, Web of Science, Cochrane library,Scopus, SID, and Magiran were searched using keywords such as menopause, hot flashes, Salviaofficinalis, and herbal medicines; all possible combinations of these words were used with the Booleanoperators of "OR" and "AND". To evaluate the quality of articles, we used Cochrane's Risk of biastools.Results: After eliminating the duplicates, a total of 148 articles were found. Following the exclusion ofirrelevant articles, 4 studies with number of 310 people were examined. Among them, 3 out of 4 studiesexamined the effect of Salvia officinalis on the frequency of hot flashes, 3 out of 4 studies examinedthe severity of hot flashes, and only 1 out of 4 studies examined the effect of Salvia officinalis on theduration of hot flashes. All 4 reviewed studies indicated that the use of Salvia officinalis reduced thefrequency and severity of hot flashes in postmenopausal women. Meta-analysis results showed that theeffect of Salvia Officinalis on the frequency [ES=-1.12 (%95 CI:-2.37; 0.14), I2=71%] of hot flashes inpostmenopausal women was significant compared to placebo, but severity [ES=-2.05 (%95 CI:-6.53;2.43), I2=70%] was not significant.Conclusion: Salvia officinalis can be used to reduce the frequency of menopausal hot flashes. Expansiveuse of this plant can be suggested in case it is confirmed in further investigations.